Melorheostosis with renal arterio-venous malformation: A case report with review of literature - Lone, Abdul Rashid; Ahmad, Mushtaq; Aziz, Sheikh Aejaz; Bhat, Gul Mohammad; Bhat, Javid Rasool; Jahan, Rifat; Khan, Shoukat H (Indian Journal of Medical and Paediatric Oncology, 2009)
Melorheostosis, also known as Leri′s disease and flowing periosteal hyperostosis, is a rare cause of pain and stiffness in a limb. The appearance is of "candle greasing" down one side of one or several bones of the body. We describe a case referred to tertiary care center with suspicion of renal cell carcinoma with diffuse bone metastasis. After reassessment, the patient was diagnosed melorheostosis with renal AV malformation. He was reassured about the benign nature of the disease and is asymptomatic.
Keywords: Flowing periosteal hyperostosis; Leri′s disease; melorheostosis; renal AV malformation